2006
DOI: 10.1111/j.1471-4159.2006.03937.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene–environment interactions in sporadic Parkinson's disease

Abstract: Much has been learned

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 193 publications
(325 reference statements)
0
45
0
Order By: Relevance
“…GST detoxified agents are, for example, polycyclic aromatic hydrocarbons, which may be found in pesticides 11 . Therefore, individuals with null genotype for GSTM1 and GSTT1 have a higher risk for oxidative stress associated diseases 12,29 , including PD 10,16 . However, there is little research on this matter, and even less on Brazilian individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GST detoxified agents are, for example, polycyclic aromatic hydrocarbons, which may be found in pesticides 11 . Therefore, individuals with null genotype for GSTM1 and GSTT1 have a higher risk for oxidative stress associated diseases 12,29 , including PD 10,16 . However, there is little research on this matter, and even less on Brazilian individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that polymorphism in enzymes involved in oxidative metabolism and detoxification could be involved in predisposition to PD. Studies have hypothesized that individuals with poor metabolizing status, based on cytochrome P4502D6 (CYP2D6) genotype could be at risk to PD 9 , though inconsistencies have been reported in the literature 10 . Similarly, polymorphism in enzymes, which generate free radicals or those involved in dopamine neurotransmission such as cytochrome P450 2E1 (CYP2E1), glutathione S-transferases (GST), superoxide dismutase (MnSOD), monoamine oxidase-B (MAO-B), dopamine receptor D2 (DRD2) and dopamine transporter (DAT) which are known to interact with environmental exposures, could be implicated in the pathogenesis of PD 1,11 .…”
mentioning
confidence: 99%
“…Examples include Huntington's disease, for which patients with the same polyQ length can exhibit variation in age of disease onset (Wexler et al 2004), Parkinson's disease, in which post-industrial environmental exposures such as insecticides have been correlated with disease onset (Benmoyal-Segal and Soreq 2006), and ALS, in which the majority of the cases are sporadic (Bruijn et al 2004).…”
Section: Small Molecule Effectors Of Neuronal Excitation As Modulatormentioning
confidence: 99%
“…The majority of cases of PD are idiopathic, likely arising from different combinations of genetic and environmental factors (Benmoyal-Segal and Soreq, 2006). Mutations in the PARK genes lead to rare, familial, mendelian parkinsonism and have provided convergence on cellular processes that might be defective in all PD sufferers (Lesage and Brice, 2009).…”
Section: Ons Cells As a Model For Pdmentioning
confidence: 99%